Reduced central line infection rates in children with leukemia following caregiver training: A quality improvement study. Issue 25 (June 2016) - Lo Vecchio, Andrea; Schaffzin, Joshua K.; Ruberto, Eliana; Caiazzo, Maria Angela; Saggiomo, Loredana; Mambretti, Daniela; Russo, Danila; Crispo, Sara; Continisio, Grazia Isabella; Dello Iacovo, Rossano; Poggi, Vincenzo; Guarino, Alfredo
Abstract : Abstract: Infections are a leading cause of morbidity and mortality in children with acute leukemia. Central-line (CL) devices increase this population's risk of serious infections. Within the context of a quality improvement (QI) project, we tested the effect of caregiver education on CL management on the CL-associated bloodstream infection (CLABSI) rate among children with acute leukemia seen at a large referral center in Italy. The intervention consisted of 9 in-person sessions for education and practice using mannequins and children. One hundred and twenty caregivers agreed to participate in the initiative. One hundred and five (87.5%) completed the training, 5 (4.1%) withdrew after the first session, and 10 (8.3%) withdrew during practical sessions. After educational intervention, the overall CLABSI rate was reduced by 46% (from 6.86 to 3.70/1000 CL-days). CLABSI rate was lower in children whose caregivers completed the training (1.74/1000 CL-days, 95% CI 0.43–6.94) compared with those who did not receive any training (12.2/1000 CL-days, 95% CI 7.08–21.0, P < 0.05) or were in-training (3.96/1000 CL-days, 95% CI 1.98–7.91) at the time of infection. Caregiver training in CL management, applied within a multifaceted QI approach, reduced the rate of CLABSI in children with acute leukemia. Specific training and active involvement of caregivers in CL management may be effective to reduce CLABSI in high-risk children. Abstract : Supplemental Digital Content is available in the text